2020
DOI: 10.5817/cp2020-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Compare and despair or compare and explore? Instagram social comparisons of ability and opinion predict adolescent identity development

Abstract: Whilst there is an emerging literature concerning social comparisons on social networking sites (SNSs), very little is known about the extent to which such behaviours inform adolescent identity. Drawing upon the three-factor model of identity development (Crocetti, Rubini & Meeus, 2008), this study seeks to determine the relationship between Instagram comparisons of ability and opinion and three identity processes: commitment, in-depth exploration, and reconsideration of commitment. 177 British adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
(53 reference statements)
2
14
1
Order By: Relevance
“…Thus, individuals evaluate a person's opinion and ability by comparing themselves with others, or socalled social comparison (Myers, 2016). This leads individuals to look back on their progress, hinders explorations of identity, and reduces commitment (Noon, 2020). This study supported the findings of a previous study (Hasanati & Aviani, 2020) for the results of this study showing that there is a relationship between social comparison and self-esteem in Instagram users, where social comparisons correlated negatively and not significantly.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, individuals evaluate a person's opinion and ability by comparing themselves with others, or socalled social comparison (Myers, 2016). This leads individuals to look back on their progress, hinders explorations of identity, and reduces commitment (Noon, 2020). This study supported the findings of a previous study (Hasanati & Aviani, 2020) for the results of this study showing that there is a relationship between social comparison and self-esteem in Instagram users, where social comparisons correlated negatively and not significantly.…”
Section: Methodssupporting
confidence: 91%
“…Social comparison is comparing oneself with other similar people and avoiding false role models that cannot be reached in their online network (Noon, 2020) [16]. Festinger et al (in Noon, 2020) divides social comparisons into two main forms: (a) Social comparisons of ability, namely comparisons of achievement and performance when individuals try to determine how well they are doing relative to others, to judge and compete with.…”
Section: Social Comparisonmentioning
confidence: 99%
“…Age (18–27), gender (Male = 0; Female = 1), and ethnicity (White British = 0; Non-White British = 1) (W1) were also entered as control variables for predicting all dependent variables (W2). Furthermore, as previous research has identified gender differences in terms of the implications of social comparisons on SNSs (e.g., Noon, 2020), we controlled for this effect by modelling paths between upward comparisons × gender and downward comparisons × gender (W1) and the three identity processes (W2). Finally, covariances were estimated between all independent variables, between the residual variances of the dependent variables, and between the error terms of the same items/parcels across both waves.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research regarding the identity implications of performance-related comparisons on SNSs supports the idea that age could be an important moderating factor. For instance, research with adolescent samples has found that such comparisons tend to associate with positive identity-related outcomes (i.e., increased commitment and in-depth exploration) (e.g., Noon, 2020), whilst studies with emerging adult samples have consistently reported negative outcomes (i.e., rumination and the diffuse-avoidant identity style) (e.g., Yang et al, 2018a). Furthermore, one cross-sectional study has tested the moderating effect of age with a sample of adolescent and emerging adult participants (Noon et al, 2021), and age was found to moderate the concurrent relationships between non-directional performance-related comparisons on Instagram and commitment and in-depth exploration.…”
Section: Social Comparisons On Instagram and Identity Developmentmentioning
confidence: 99%
See 1 more Smart Citation